Patterns of behavior in the crawl technique of the elite Portuguese swimmers - Ricardo, N.; Milheiro, V.; Branco, M.; Campanico, J.; Freitas, J.; Conceicao, A.; Louro, H.; Silva, A. (Biomechanics and Medicine in Swimming XI - Abstracts, 2010)
INTRODUCTION: The purpose of this study was to find the applicability of the monitoring system based on the crawl technique. Louro et al. (2009) found that the existence of motor patterns contributes for the implementation of this technique, from an appropriate observed methodology. When used in swimmers training, analysis can reduce the variability of behavioral tuning swimming technique (Campanico, et al. 2006). The behavior was studied through the analysis of temporal patterns (Tpattern) of five elite swimmers and a sequence of five cycles (swimming at submaximal (75%) and maximum speed). METHODS: Five elite Portuguese swimmers (Mean ± SD; age 20,87 ±1,55; FINA Points at 100m crawl: 815,62 ±65,09), performed the distance of 25 meters, at submaximal (75%) and maximum speed. A digital video camera Sony Mini DV (25 Hz) was placed about 30 centimeters deep, near the edge of the pool. The instrument of observation was prepared Ad-Hoc qualitative analysis, enables the study of stability of technical implementation. This study was ensured through the index of intra-observed reliability (95%) and interobserved accuracy (96%). The Theme 5.0 software was used to detect patterns of 5 cycles in each swimmer. This allowed the identification of stable structures in technical performance, within a critical interval of time (P<0.05) - T - patterns. RESULTS: The mean index values of stability in the sub-maximum speed were 0.45 ± 0.16, and the relative to the values of stability at maximum speed was 0.43 ± 0.12. DISCUSSION: the swimmers with best times have an improved stability of swimming in the two executions, although this is higher in sub-maximum speed, we deduce that it´s because the sub-maximal speeds are closer to the training speed.